2003
DOI: 10.1111/1468-5957.05421
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Relevance of Cash Flow and Accrual Information for Solvency Assessments: A Multi‐Method Approach

Abstract: This multi-method study reports the results of two complementary experiments investigating the relevance of cash flow and accrual information. A behavioural field experiment investigated differences in the accuracy of solvency assessments between commercial lending managers using cash flow information and those using accrual information. Results indicated that commercial lending managers using cash flow information made more accurate solvency assessments than managers using accrual information. Results of an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
(66 reference statements)
1
10
0
1
Order By: Relevance
“…Lenders should consider these differences between the models. The differences between models concur with Mear and Firth (1987) as well as Sharma and Iselin (2003), who suggest that humans are more fallible because they tend to overestimate the less relevant cues and underestimate the more relevant ones. In addition, the results align with Zacharakis and Shepherd (2001) who state that VCs are too confident in their assessment of a start-up when they predict a very high level of success.…”
Section: Resultssupporting
confidence: 86%
“…Lenders should consider these differences between the models. The differences between models concur with Mear and Firth (1987) as well as Sharma and Iselin (2003), who suggest that humans are more fallible because they tend to overestimate the less relevant cues and underestimate the more relevant ones. In addition, the results align with Zacharakis and Shepherd (2001) who state that VCs are too confident in their assessment of a start-up when they predict a very high level of success.…”
Section: Resultssupporting
confidence: 86%
“…PCA is mainly used in combination with neural networks (Mensah, 1984;Zavgren, 1985;Gombola et al 1987;Skogsvik 1990;Alici, 1996;Sharma and Iselin, 2003;Shin and Lee, 2003;Wang, 2004;Canbas et al, 2005;Min and Lee, 2005;Tang and Chi, 2005;Shin et al, 2006;Sookhanaphibarn et al, 2007;Yao, 2007. Ravi andPramodh, 2008;Chen and Du 2009;Balas et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As lenders, banks prefer to employ cash flow statements of borrowers when banks make credit decisions and evaluate risks. Studies demonstrated that the accuracy of assessing borrowers' solvency differs among lending managers of commercial banks who use cash flow data compared to those who use earnings data (Sharma and Iselin, 2003;Curtis et al, 2020).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%